Isolation of living dopaminergic neurons labeled with a fluorescent ligand of the dopamine transporter from mouse substantia nigra as a new tool for basic and applied research - Troshev, Dmitry; Blokhin, Victor; Ukrainskaya, Valeria; Kolacheva, Anna; Ugrumov, Michael (Frontiers in Molecular Neuroscience, 2022)
Dopaminergic neurons (DNs) of the nigrostriatal system control the motor function, and their degeneration leads to the development of Parkinson’s disease (PD). A stumbling block in the study of DNs in the whole substantia nigra (SN) is the lack of tools to analyze the expression of most of the genes involved in neurotransmission, neurodegeneration, and neuroplasticity, since they are also expressed in other cells of the SN. Therefore, this study aimed to develop a fluorescence-activated cell sorting method for isolating living DNs from the SN of wild-type mice using two fluorescent dyes, DRAQ5 (nuclear stain) and a dopamine uptake inhibitor GBR 12909 coupled to a fluorophore (DN stain). We have developed a method for selecting a population of DNs from the SN of mice, as evidenced by: (i) immunopositivity of 95% of the sorted cells for tyrosine hydroxylase, the first enzyme of dopamine synthesis; (ii) the sorted cells expressing the genes for specific proteins of the dopaminergic phenotype, tyrosine hydroxylase, the dopamine transporter, and vesicular monoamine transporter 2 and non-specific proteins, such as aromatic L-amino acid decarboxylase, non-specific enzyme of dopamine synthesis. We then compared the changes in gene expression found in the sorted DNs and in the SN homogenate in a PD model we developed, reproduced in mice by treatment with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). Using quantitative PCR, we obtained evidence of the same changes in the expression of specific genes in the sorted DNs of SN and in the SN homogenate of a MPTP mouse model of PD, compared with the control. The undoubted advantage of our approach is the possibility of obtaining a large amount of readily available and relatively cheap primary material (SN) from wild-type mice, which can be used to solve both research and applied problems. In addition, this method can be easily adapted to the isolation of DNs from the SN in other animal species, including non-human primates.